Nonlinear Moment-Tensor Inversion of Repetitive Long-Periods Events Recorded at Pacaya Volcano, Guatemala - Lanza, Federica; Waite, Gregory P. (Frontiers in Earth Science, 2018)
Detailed models of low-frequency seismicity at volcanoes provide insights into conduit structure and dynamics of magmatic systems. Many active volcanoes produce repetitive seismic events, but these are often too small to model on their own. Here we examine thousands of repetitive explosion-related long-period (LP) events from Pacaya volcano, Guatemala, that were recorded during a temporary installation of four broadband seismic stations from October to November 2013. As most of the LP events are buried in background tremor, we used a matched filter from the higher signal-noise infrasound expression from these events. We derive a representative seismic signal from the phase-weighted stack of 8,587 of these events, and invert for a source moment tensor. To address the limitations posed by the number of stations of the local network, we employ a nonlinear waveform inversion that uses a grid search for source type to obtain a quantitative measure of the source mechanism reliability. With only four stations, Pacaya represents a case of limited observational data, where a quantitative description of moment-tensor uncertainty is needed before any interpretation is to be attempted. Results point to a shallow source mechanism somewhat like a tension crack, dipping 40° to the east, consistent with the dominant E-W motion in the seismic records. The uncertainties determined from the nonlinear inversion are not insignificant, but clearly constrain the mechanism to be a source dominated by isotropic components. The N-S orientation of the modeled crack is parallel to surface features and the dominant dikes modeled in numerous geodetic studies, suggesting the conduit may be elongated N-S throughout most of its path through the edifice. Our study demonstrates that by stacking thousands of small LP events they can be modeled to build understanding about conduit structure.